Impact of Modified Diet, Swallowing Exercises, and Neuromuscular Electrostimulation on Severity of Oropharyngeal Dysphagia of Geriatric Patients - Margarita Rugaitienė; Vita Lesauskaitė; Ingrida Ulozienė; Gerda Kalinauskaitė; Marius Juška; Gytė Damulevičienė (Medicina, 2024)
Background and Objectives: Oropharyngeal dysphagia is a common swallowing disorder, characterized by difficulties in moving food and liquids from the mouth to the esophagus; it is particularly prevalent among older adults with neurological conditions. This study aimed to evaluate the effectiveness of a short-term complex treatment protocol combining dietary modifications, swallowing exercises, and transcutaneous neuromuscular electrostimulation in reducing the oropharyngeal dysphagia severity and aspiration risk among geriatric patients. Materials and Methods: A total of 64 participants aged 60 and older, with oropharyngeal dysphagia, at LSMU Kaunas Hospital between May 2021 and April 2023, were included in the study after excluding those with significant comorbidities. Diagnostic assessments included the water swallow test and Fiberoptic Endoscopic Evaluation of Swallowing, conducted before and after treatment. Results: The results indicated a statistically significant reduction in the severity of oropharyngeal dysphagia, with 18.8% of patients showing improvements from moderate to mild dysphagia and 33.3% from severe to moderate. Additionally, the median PAS score was four points (IQR 3–6) before treatment and significantly decreased to three points (IQR 2–4) after treatment (p < 0.001). Conclusions: These findings suggest that even a short-term multidisciplinary approach that lasts 10 days can effectively alleviate the symptoms of oropharyngeal dysphagia, enhance patient safety, and improve swallowing among geriatric patients suffering from this condition.